Cost-Utility of Real-Time Potassium Monitoring in United States Patients Receiving Hemodialysis - Ryan J. Bamforth; Thomas W. Ferguson; Navdeep Tangri; Claudio Rigatto; David Collister; Paul Komenda (Kidney International Reports)
Introduction: Patients with kidney failure requiring hemodialysis are at high risk for hyperkalemia between treatments, which is associated with increased cardiovascular morbidity and mortality. Early detection of hyperkalemic events may be useful to prevent adverse outcomes and their associated costs. We performed a cost-utility analysis comparing an intervention where a real-time potassium monitoring device is administered in patients on hemodialysis in comparison to usual care. Methods: We developed a cost-utility model with microsimulation from the perspective of the United States health care payer. Primary outcomes included the monthly cost-effectiveness threshold cost and break-even cost per patient attributable to the intervention and the incremental cost-effectiveness ratio comparing the intervention to usual care. A 25% reduction in hyperkalemic events was applied as a baseline device effectiveness estimate. Concurrent first and second order microsimulations were performed using 10%, 25%, and 50% effectiveness estimates as sensitivity analyses. Results are presented over a 10-year time horizon in 2022 United States dollars and a willingness-to-pay threshold of $100,000 per quality-adjusted life year (QALY) was considered. Results: Over 10 years, threshold and break-even analysis yielded maximum monthly costs of $201.10 and $144.15 per patient, respectively. The intervention was associated with reduced mean costs ($6381.21) and increased mean QALYs (0.03) per patient; therefore, was considered dominant. In sensitivity analysis, the intervention was dominant in 99% of simulations performed at all effectiveness rates. Conclusion: Implementing a real-time potassium monitoring device in patients on hemodialysis has the potential for cost savings and improved outcomes from the perspective of the United States health care payer.